Student teachers' preparation for inclusive education : the case of the University of Limpopo - Sepadi, M. D. (My University, 2018)
The purpose of this study is to describe the extent to which universities prepare student teachers for inclusive education implementation, using University of Limpopo as a case. The study followed a qualitative research approach where a case study design was adopted. The study population consisted of all the third year students in the school of education. Eight student teachers were recruited to participate in the study through a purposive sampling strategy. The data was collected through two methods, namely interviews and document analysis. The data was analysed through thematic content analysis where themes were developed based on the verbatim transcripts from the data collected. The study came out with six findings namely: Lack of a clear understanding of what inclusive education is, lack of comprehensive course material, lack practical experience (the gap between theory and practise), no clear policies on teaching, learning and assessment in inclusive education, teaching strategy used by the lecturer is ineffective; and unpreparedness in teaching a diverse classroom. These findings implicate that the current training is insufficient to prepare students to effectively implement inclusive education. The study recommends that the current program be revised and repacked in order to advance the ideals of inclusive education in South Africa
Thesis (M. Ed.) --University of Limpopo, 2018
Keywords: Inclusive education; Student teachers; Teacher education; College students.; Teacher-Students.; Inclusive education -- South Africa